SDS-polyacrylamide-gel electrophoresis of sperm proteins of buffalo and cattle bulls - KULKARNI, B A; RUPAL, R K; HEGOE, UMASHASHI C (The Indian Journal of Animal Sciences, 2013)
Sperm protein patterns in buffalo and cattle breeding bulls were analysed by SDS-PAGE. Buffalo and cattle bull spermatozoa had 21 and 23 protein bands of varying intensities and molecular weight ranging from> 100 to 13 KDa. Distinct species differences in sperm protein patterns were observed. A major protein of molecular weight 16 KDa and a broad protein band having molecular weight below 14 KDa were present in cattle spermatozoa but absent in buffalo spermatozoa. Individual variations and distinct breed differences in sperm protein patterns of Hiolstein-Friesian. Jersey and crossbred cattle bulls and Murrah and Surti buffalo bulls were observed.